Changes in maternal morbidity and infant outcomes following state-level abortion bans post-Dobbs: a comparative interrupted time series study - Laura Gressler; Kanna Lewis (BMC Public Health)
Abstract Background The Supreme Court’s decision in Dobbs v. Jackson Women’s Health Organization overturned the Roe v. Wade precedent, significantly altering abortion access across the United States (U.S.). This ruling enabled states to regulate, limit, or ban abortion, resulting in millions of women losing access to abortion services and potentially affecting birth outcomes. This study aimed to assess the impact of the Dobbs decision on birth outcomes in states with and without abortion bans. Methods A retrospective cohort analysis applied comparative interrupted time series to assess the difference in changes in adverse birth outcomes pre-and post-Dobbs across abortion legislation status. Natality data from the CDC WONDER database was analyzed. States were classified based on the presence or absence of abortion bans as of June 24, 2022. Proportions of non-living births, births with congenital anomalies, and maternal morbidities among U.S. births between January 2021 and February 2024 were examined. Results No statistically significant difference in non-living births was observed between states with and without abortion bans. In states with abortion bans, the rate of births with congenital anomalies increased slightly post-Dobbs but the increase was not statistically significant. States without bans saw a decrease of 2 per 10,000 births (p < 0.001) from the baseline. The difference in the change in congenital anomalies between states with and without bans was 4.3 per 10,000 births (p = 0.015). States with abortion bans did not experience significant changes in maternal morbidity rates post-Dobbs, while states without bans experienced an increase of 4.8 per 10,000 births (p < 0.001). The difference between the changes in maternal morbidity rates was 4.5 per 10,000 births (p = 0.014). Conclusions The Dobbs decision has led to divergent birth outcomes in states with and without abortion bans. States without bans experienced a decrease in congenital anomalies and an increase in maternal morbidity rates, while the proportion of these adverse birth outcomes were unchanging in states with bans. Although a direct evidence of abortion bans increasing adverse birth outcomes was not found, the difference in the changes in congenital anomalies across abortion policies suggests that there is a potential for the exacerbation of inequities and further investigation is warranted.